1977
DOI: 10.1042/bj1640229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biliary excretion of the four isomers of bilirubin-IX in Wistar and homozygous Gunn rats

Abstract: The biliary excretion of the four isomers of bilirubin-IX was studied in Wistar rats (JJ) and homozygous Gunn rats (jj). Synthetic preparations of 14C-labelled pigments were used. 1. After intravenous administration, the alpha-isomer was rapidly excreted in conjugated form in bile of Wistar rats. In Gunn rats excretion was insignificant. In contrast, both rat species promptly excreted the non-alpha-isomers at rates that were comparable with that found for bilirubin-IXalpha in Wistar rats. 2. In normal rats abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 24 publications
(39 reference statements)
4
32
0
Order By: Relevance
“…After injection of [3H]bilirubin, extraction and TLC of labeled pigments in bile showed that at least 98% of all radioactivity was present in conjugated bilirubin; labeled bilirubin degradation products could not be detected. Cumulative excretion in bile of the injected dose of [3H]bilirubin was 94.0±0.2% in 2 h, which compared favorably with previously published findings (44,45).…”
Section: Deconjugation Of Bmg In Vivosupporting
confidence: 80%
“…After injection of [3H]bilirubin, extraction and TLC of labeled pigments in bile showed that at least 98% of all radioactivity was present in conjugated bilirubin; labeled bilirubin degradation products could not be detected. Cumulative excretion in bile of the injected dose of [3H]bilirubin was 94.0±0.2% in 2 h, which compared favorably with previously published findings (44,45).…”
Section: Deconjugation Of Bmg In Vivosupporting
confidence: 80%
“…In two Gunn rats, only 4 and 5%, respectively, of injected Illa or XIIIa isomer was recovered in bile in 3 h and bilirubin glucuronides could not be detected. These results are similar to those obtained with bilirubin (29), and show that Gunn rats are unable to conjugate bilirubin-IIIa and -XIIIa. In four SpragueDawley rats injected with equal amounts of [3H]bilirubin monoglucuronide and either [14C]bilirubinIlla or -XIIIa monoglucuronide, recovery of 14C in the bile collected for 2 h ranged from 81 to 91% of the administered dose; the corresponding values for 3H recovery were 74-90%.…”
Section: Experimental Series Isupporting
confidence: 80%
“…[14C]hilirubin-IIIa, -IXa, -XIIIa (30-60 nmol) was administered to normal or homozygous Gunn rats and biliary excretion of these three isomers determined as descrihed (29). In addition, excretion in bile of 3H-and 14C-labeled BMG and BDG was measured in fouir rats injected intravenously with a mixture of 75 Series III.…”
Section: Specific Experimentsmentioning
confidence: 99%
“…Regarding bile pigments, although the IXβ isomer of bilirubin constitutes only a small fraction of the total amount produced in the fetus [33] , this more water-soluble isomer is the most abundant isomer found in fetal gallbladder bile and meconium [34,35] . The reason for this is two-fold: (1) bilirubin IXβ cannot easily cross the placenta; and (2) it can be excreted into bile without previous conjugation with glucuronic acid [36] .…”
Section: The Hepatobiliary Excretory Function During Intrauterine Lifementioning
confidence: 99%